A modified non-dissipative LC snubber circuit for MOSFET based fly-back converters. (2nd December 2009) - Chatterjee, Debashis; Ganguli, A.K.; Chakrabarti, R.; Bharatkar, S.S.
High frequency converters with different switching topologies are now being widely used over a wide range of applications, which mainly includes different types of power supplies. Snubber circuit design for high frequency-switched converters using MOSFET as a power device assumes different dimension as regards the minimisation of the power dissipation in the snubber resistance. This paper shows a different mode of operation to reduce the clamp voltage across the device used in fly-back type converter. The LC snubber circuit is almost lossless and of energy regenerative type. A reduced clamp voltage is required not only for device protection, but also to reduce the cross regulation effect in multiple output converters. Simulations and experimental results validate the concept.